Menegakkan Prinsip Keadilan dan Kejujuran dalam Demokrasi : Berani Tolak Politik Uang - Merlindang Simamora; Bolivia Renata Sianipar; Balqis Zhofayra Alya; Raihan Ananda Azma; Jennifer Olivia Annisa Putri; Hairunisa Astari; Jelvan Andi Putra Lase; Taufiq Ramadhan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
A healthy democracy must be based on the principles of justice and honesty, especially in the implementation of elections as a form of public participation. However, money politics remains a major issue in Indonesia’s 2024 regional elections (Pilkada), threatening the integrity of democracy. This study employs a qualitative descriptive approach with literature review and secondary data analysis from official reports and surveys to describe the dynamics of money politics and evaluate its handling. The findings reveal various forms of money politics, including cash distribution, goods, and digital transfers aimed at influencing voters. The main causes include low political awareness, permissive culture, and weak supervision and law enforcement. The study emphasizes the importance of synergy between strict regulations, effective monitoring by Bawaslu, voter education, and active public participation to eradicate money politics and realize clean and democratic elections.